Changes in peripheral blood lymphocytes in polycythemia vera and essential thrombocythemia patients treated with pegylated-interferon alpha and correlation with JAK2V617F allelic burden. Issue 1 (December 2015) - Kovacsovics-Bankowski, Magdalena; Kelley, Todd; Efimova, Olga; Kim, Soo; Wilson, Andrew; Swierczek, Sabina; Prchal, Josef
Abstract Background Pegylated-interferon alpha (PegINFα) treatment of patients with polycythemia vera (PV) and essential thrombocythemia (ET) has resulted in long-term clinical response, decreasedJAK2 V617F allelic burden and restoration of polyclonal hematopoiesis. The mechanisms of the beneficial effects of PegINFα are not clear, but available evidence suggests direct suppression ofJAK2 -mutated clone, induction of dormant stem cells to proliferation, and augmentation of an immune effect against PV and ET clones. Methods We analyzed the phenotype and frequency of peripheral blood lymphocytes (PBL) from PegINFα treated patients and compared them to patients treated with hydroxyurea (HU). Samples collected at various time points before and during treatment were analyzed using multicolor flow cytometry. Results We found that PegINFα increased the frequency of peripheral blood CD4+ Foxp3+ regulatory T cells (Treg). Highly suppressive Treg, characterized by co-expression of CD39 and HLA-DR, were also increased in PBL from PegINFα treated patients. We observed an augmentation of cycling CD8+ T cells, NK cells, and of poorly activated CD38+ CD8+ T cells. Our results also suggest that PegINFα increased the frequency of PD-1+ CD4+ helper cells and PD-1+ CD4+ Foxp3+ Treg cells. None of these changes were present in HU treated patients. We analyzed the correlation between changes in different T cell populations in the peripheral blood with the changes inJAK2 V617F allelic burden in clonal granulocytes. Augmentation of Ki-67+ Treg, HLA-DR+ CD39+ Treg, Helios+ Treg and HLA-DR+ CD38+ CD8+ T cells correlated with an increase inJAK2 V617F allelic burden. We also found a positive correlation between PD-1+ Treg andJAK2 V617F allelic burden; however, the number of available patients was small (n = 7). Conclusions We report marked changes in frequencies of PBL subsets after PegINFα treatment, suggesting an immunomodulatory effect by PegINFα. Generation of a more suppressive immune response, as measured by an increase in highly suppressive Treg and poorly activated CD8+ T cells, correlated with a poor molecular response. In this study, we have not identified changes in the PBL that would indicate the presence of an effective anti-tumor response.Trial registration NCT01259856, December 7. 2010 and NCT01259817, December 6. 2010, Grant #1P01CA108671-O1A2, July 17. 2006, Sponsor: MPDRC/NIH, NCI-2012-00269, January 12. 2011 and NCI-2012-00268, January 12. 2011